IMPORTANCE OF SLAMET RIYADI VALUES IN THE FOURTH INDUSTRIAL REVOLUTION ERA - Fitri Warna Sari (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
We are currently in the Fourth Industrial Revolution era. The fourth Industrial Revolution era is closely related to technological developments, especially in the field of digitalization or new media. Changes in people's lifestyles in this era of technological development affect many things, for example how to communicate, seek information, study, shop, buy food, order motorcycle taxis and other life activities that are carried out completely online. Broadly speaking, this turns individuals into people who are lazy to move and want everything to be done with just a touch. On the other hand, the progress of the 4.0 industrial revolution also has a major impact on the progress of the nation and the State, of course, if these changes can be directed towards positive things. One of the positive values that is indispensable is the inculcation of the Slamet Riyadi’s values in each individual. The Slamet Riyadi’s value is a form of behavior that reflects a hero character who has extraordinary exemplary, brave, steadfast in his stance and still holds his duties even though his body is injured or there is an opportunity for ease in carrying it out. In this context, changes in people's behavior arise from technological developments, because of the ease of getting something, individuals behave in an instant and create a weak mentality. By instilling Slamet Riyadi's value in each individual, negative behavior changes from the development of media and technology can still be controlled and directed towards positive things. Cultivating the of Slamet Riyad’s Value certainly starts from the individual's awareness to understand and control oneself. Meanwhile, for children, the role of parents is very important to instill the value of religious safety from an early age, so that they can be controlled in following technological developments. Keywords: Fourth Industrial Revolution, new media and Slamet Riyadi Value